Expression and function of p-glycoprotein in normal tissues: effect on pharmacokinetics - Staud, Frantisek; Ceckova, Martina; Micuda, Stanislav; Pavek, Petr (Methods in molecular biology (Clifton, N.J.), 2010)
ATP-binding cassette (ABC) drug efflux transporters limit intracellular concentration of their substrates by pumping them out of cell through an active, energy dependent mechanism. Several of these proteins have been originally associated with the phenomenon of multidrug resistance; however, later on, they have also been shown to control body disposition of their substrates. P-glycoprotein (Pgp) is the first detected and the best characterized of ABC drug efflux transporters. Apart from tumor cells, its constitutive expression has been reported in a variety of other tissues, such as the intestine, brain, liver, placenta, kidney, and others. Being located on the apical site of the plasma membrane, Pgp can remove a variety of structurally unrelated compounds, including clinically relevant drugs, their metabolites, and conjugates from cells. Driven by energy from ATP, it affects many pharmacokinetic events such as intestinal absorption, brain penetration, transplacental passage, and hepatobiliary excretion of drugs and their metabolites. It is widely believed that Pgp, together with other ABC drug efflux transporters, plays a crucial role in the host detoxication and protection against xenobiotic substances. On the other hand, the presence of these transporters in normal tissues may prevent pharmacotherapeutic agents from reaching their site of action, thus limiting their therapeutic potential. This chapter focuses on P-glycoprotein, its expression, localization, and function in nontumor tissues and the pharmacological consequences hereof.
Keywords: biologický transport; Tissue Distribution; ATP Binding Cassette Transporter, Subfamily B, Member 1; těhotenství; Intestine, Small; Biological Transport; mužské pohlaví; placenta; tenké střevo; mozek; Placenta; testis; polymorfismus genetický; P-glykoprotein; Polymorphism, Genetic; Brain; ženské pohlaví; zvířata; tkáňová distribuce; Humans; Xenobiotics; Pregnancy; xenobiotika; ledviny; Kidney; Female; Testis; lidé; Male; Animals